Questioning God in the Wake of Sexual Abuse: A Political Theology of Healing - Cinocca, Federico (Lumen et Vita, 2023)
This paper considers the engagement of Christian communities in the healing process of the victims after cases of sexual abuse. Over the last fifty years, restorative justice has emerged to respond to the harm inflicted on individuals by abusive behaviors. However, restorative justice alone, focusing on restoring the relationship between the victim and the aggressor, leaves many social and institutional mechanisms unchallenged. Drawing on Johann B. Metz’s political theology, I claim that three aspects must be taken into account by Christian communities to show solidarity with the victims and facilitate their spiritual healing: the necessity of structural change through serious consideration of social sin in the Church; the importance of parrhesia (open and honest speech) through peaceful public protests where survivors and their allies manifest their discontent and ask for accountability; listening to the marginalized as a priority that re-educates the Church to pay attention to those who suffer.